2018
DOI: 10.1002/aenm.201802263
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Indium‐Based Ternary Thiospinel as Conceivable High‐Potential Air‐Cathode for Rechargeable Zn–Air Batteries

Abstract: Reversible oxygen reactions in Zn–air batteries require cost‐effective and highly‐active bifunctional electrocatalysts to substitute traditional noble‐metal based catalysts. Herein, a new and promising electrocatalytic material, ternary CoIn2S4 thiospinel, is demonstrated for effectively catalyzing oxygen reduction and oxygen evolution reactions (ORR and OER) with S‐doped reduced graphene oxide (S‐rGO) as an electronic conductor. Compared with Co9S8/S‐rGO (without In doping), the newly developed CoIn2S4/S‐rGO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
113
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 252 publications
(116 citation statements)
references
References 71 publications
3
113
0
Order By: Relevance
“…To overcome these two fundamental problems, technologies developed have to be centered upon achieving a sustainable means for fuel generation as well as focused on achieving carbon neutrality, whereby the net carbon footprint amounts to zero and CO 2 emissions into the atmosphere are largely offset by the removal or conversion of atmospheric CO 2 . [ 14–17 ] Scientific research, over the decades, has identified several key methods for the conversion of CO 2 , classified into biological, chemical, electrochemical, photocatalytic, reforming, and inorganic transformations. [ 18–20 ] This review focuses on the renowned and promising technologies of electrochemical and photocatalytic CO 2 reduction for their great potential in effectively driving conversion of CO 2 into other derivative forms of value‐added fuel.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these two fundamental problems, technologies developed have to be centered upon achieving a sustainable means for fuel generation as well as focused on achieving carbon neutrality, whereby the net carbon footprint amounts to zero and CO 2 emissions into the atmosphere are largely offset by the removal or conversion of atmospheric CO 2 . [ 14–17 ] Scientific research, over the decades, has identified several key methods for the conversion of CO 2 , classified into biological, chemical, electrochemical, photocatalytic, reforming, and inorganic transformations. [ 18–20 ] This review focuses on the renowned and promising technologies of electrochemical and photocatalytic CO 2 reduction for their great potential in effectively driving conversion of CO 2 into other derivative forms of value‐added fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The spinel structure is known to be flexible and allows an accommodation of 1) a variety of metallic elements with different atomic size and mass, 2) ordered or disordered arrangement of cations (so‐called normal, inverse, or intermediate structures), and 3) partially occupied crystallographic positions. All these result in a diversity of magnetic, optical, catalytic, electrical, as well as thermoelectric (TE) properties . Many spinels consisting of well‐abundant and environmental‐friendly elements (which is crucial for a possible thermoelectric application) became the object of numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that cobalt phosphide (CoP x ) is a class of excellent OER catalyst but its ORR activity is relatively low . Furthermore, doping of indium (In) with transition metals has been reported to improve the reversible oxygen electrocatalysis, as demonstrated by experimental and theoretical studies . Therefore, it is a logical strategy to achieve bifunctional oxygen electrocatalyst by the efficient integration of multiple active components into one entirety.…”
mentioning
confidence: 99%
“…As compared to In‐CoO/CoP FNS, the CoO/CoP (Figure S15, Supporting Information) and In‐CoP (Figure S16, Supporting Information) samples display inferior ORR and OER activities in terms of higher overpotentials and smaller current densities (Figure S17, Supporting Information). On the one hand, the incorporation of In element can optimize electronic structure of catalysts, facilitating the ORR and OER activities . On the other hand, the strong synergistic effect of heterostructure between CoO and CoP also enhances the ORR and OER performance …”
mentioning
confidence: 99%